Effect of sintering temperatures and foaming agent content to the physical and structural properties of wollastonite based foam glass-ceramics - Jaafar, Suhail Huzaifa; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Mohd Ghazali, Mohd Sabri; Mohd Shofri, Muhammad Faris Syazwan; Noor Hisham, Noor Aizat; Saparudin, Dur Iffa (International Institute for the Science of Sintering, 2020)
This study aims to fabricate low-cost foam glass-ceramic using soda-lime-silica (SLS) glass waste and clamshells (CS) as foaming agent in content between 1 and 12 wt.% by conventional powder processing method. The samples were undergoing sintering process between 700 and 1000 °C with holding time of 30 minutes and characterized according to the physical and structural properties. Samples containing 3 wt.% CS treated at 800 °C show the greatest size of porosity. As the sintering temperature increased, the samples tend to become less dense. However, for the samples sintered at 900 and 1000 °C, the trend of the density changes because of the excess CO2 gases generated during the heat treatment process promotes an increase in internal pressure, which results in the rupture of the pore walls. For linear expansion, for samples with a sintering temperature of 800 °C and higher, the increment of the temperature will lead to the decrement of linear expansion (%). As the sintering temperature increases from 700 to 800 °C, the water absorption (%) increases. However, the percentage of water absorption decreases with the further increment of sintering temperature. The XRD characterization showed the formation of wollastonite phase (CaSiO3) and further revealed the formation of greater peaks of CaSiO3 at the higher sintering temperatures. The results of compressive mechanical strength between 0.15 and 1.50 MPa indicate that the obtained glass-ceramic foams have potential for building material applications.